2012
DOI: 10.1007/s10646-012-0894-3
|View full text |Cite
|
Sign up to set email alerts
|

Recovery potential of periphytic biofilms translocated in artificial streams after industrial contamination (Cd and Zn)

Abstract: Metal wastes can significantly disturb aquatic communities, particularly photosynthetic organisms, the main primary producers in freshwater running ecosystems. In this study, biofilms and diatoms were used as bioindicators to characterize the kinetics of biofilm recovery. An experimental decontamination study was conducted under laboratory conditions, after biofilm colonisation at a site subject to discharge of industrial metals (Zn and Cd) and in parallel at an upstream site, metal-free, considered as a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…As suggested by Morin et al [64] and Arini et al [65], deformity frequencies between 0.5 and 1% are considered as naturally occurring. With abnormal valve frequencies of 1-1.2%, it is difficult to confirm a specific response to metal contamination at sites JC1, JC2, JC4, JC5, JC6, JC7, NC1, and NC2, as these values are close to the estimated natural background.…”
Section: Diatom Teratologies As a Response To Stressmentioning
confidence: 97%
“…As suggested by Morin et al [64] and Arini et al [65], deformity frequencies between 0.5 and 1% are considered as naturally occurring. With abnormal valve frequencies of 1-1.2%, it is difficult to confirm a specific response to metal contamination at sites JC1, JC2, JC4, JC5, JC6, JC7, NC1, and NC2, as these values are close to the estimated natural background.…”
Section: Diatom Teratologies As a Response To Stressmentioning
confidence: 97%
“…In the literature lack of recovery has been linked with retention of contaminants in the biofilm that prevents complete removal of the stress even though it is no longer present in the bulk liquid phase (Ivorra et al, 1999). For example, Arini et al (2012) used artificial streams to assess biofilm recovery following Cd and Zn exposure. After 56 days, full recovery was not observed, and lack of recovery was attributed in part, to retention of the metals in the biofilm matrix.…”
Section: Lack Of Recoverymentioning
confidence: 99%
“…While the general biomass measures appeared relatively insensitive measures of effects and recovery, the specific measures related to algal/cyanobacterial and bacterial biomass, were revealing with regard to community response to TCS exposure and recovery. Arini et al (2012) reported that diversity indices and biovolumes measured from biofilms under decontamination conditions did show the beginnings of recovery. Activity measurements include thymidine incorporation and compound-specific estimates based on labeled substrates, as well as commonly-used Biolog Ecoplate.…”
Section: What Measurements Are Best?mentioning
confidence: 99%
“…The stria density ranges from 32-47/10 µm [14]. N. palea has been described as relatively tolerant to metals [6,15] and to pesticides [16][17][18]. This taxon is considered to be one of the most pollution tolerant species.…”
Section: Algal Culturesmentioning
confidence: 99%
“…However, diatoms are sensitive to contaminants and have shown their usefulness to assess exposure to toxic agents such as metals. Many studies have investigated the responses of diatom assemblages to metal contamination (e.g., [6][7][8]), and have shown impacts at structural and functional levels. In a review paper on the effects of metals on diatoms, Morin et al [9] presented several diatom-related biological descriptors that can be of interest in monitoring metal contamination.…”
Section: Introductionmentioning
confidence: 99%